2015
DOI: 10.1186/s12947-016-0046-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of myocardial fibrosis by cardiac integrated backscatter analysis in Kawasaki disease

Abstract: Background: Kawasaki disease is an acute, systemic vasculitis that affects the coronary arteries. However, the relationship between myocardial fibrosis and Kawasaki disease has been completely unknown until now. We aimed to provide quantitative information about myocardial fibrosis using cardiac integrated backscatter in Han race Kawasaki disease patients. Methods: Ninety Kawasaki disease patients and 90 healthy control subjects were recruited. Based on Kawasaki disease status, the patients were categorized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Inflammatory cells were also observed between cardiac myocytes [2,11] that was suggestive of myocarditis which is considered as a feature of KD [9.11,13,27,28] . Myocardial fibrosis was also observed in this study in Mallory stained sections [9,11,12] . This fibrosis was explained by authors who reported that it might be due to previous ischemia in the area perfused by the affected coronary artery [9,11] .…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Inflammatory cells were also observed between cardiac myocytes [2,11] that was suggestive of myocarditis which is considered as a feature of KD [9.11,13,27,28] . Myocardial fibrosis was also observed in this study in Mallory stained sections [9,11,12] . This fibrosis was explained by authors who reported that it might be due to previous ischemia in the area perfused by the affected coronary artery [9,11] .…”
Section: Discussionsupporting
confidence: 72%
“…Myocardial ischemia remains an important concern. Some authors reported that patients with KD might be at risk of developing ischemic cardiomyopathy due to abnormal myocardial perfusion and reduced coronary flow [12] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We suppose that the reduced ejection fraction is due to subclinical myocardial fibrosis. According to some authors, myocardial fibrosis is related to previous ischemia in the area perfused by the coronary artery where an aneurysm has been present or as a sequel of myocarditis in the acute phase of the disease [33,34].…”
Section: Follow-upmentioning
confidence: 99%